302 Vessel Wall Enhancement on Magnetic Resonance Imaging After Stent-Retriever Thrombectomy. (August 2016) - Abraham, Peter; Cheung, Vincent J.; Lee, Roland; Pannell, Jeffrey Scott; Gupta, Mihir; Rennert, Robert; Khalessi, Alexander Arash
Abstract : INTRODUCTION: Animal and in vitro studies have demonstrated histologic iatrogenic endothelial injury after stent-retriever thrombectomy. However, noncontrast vessel wall magnetic resonance imaging (MRI) studies have failed to demonstrate vessel injury. Our prospective study examines iatrogenic endothelial damage after stent-retriever thrombectomy in vivo utilizing high-resolution contrast-enhanced vessel wall MRI (VW-MRI). METHODS: We evaluated 11 patients, including postthrombectomy and control subjects, on a Signa HDx 3.0-T MRI scanner with an 8-channel head coil. Pre- and postcontrast T1-weighted CUBE vessel wall images and MR angiograms were acquired with attention to the Circle of Willis. Parenchymal imaging included diffusion, susceptibility, and T2 fluid attenuated inversion recovery (FLAIR)-weighted images. The primary end point was vessel wall enhancement, as determined by 2 independent, blinded board-certified neuroradiologists before examination of parenchymal imaging. Additional covariates were age, National Institutes of Health Stroke Scale, level of occlusion, stroke etiology, devices utilized, number of passes required for thrombectomy, TICI reperfusion score, stroke volume, and 90-day modified Rankin Scale (mRS). RESULTS: Post-contrast T1-weighted vessel wall enhancement was detected in the middle cerebral artery (MCA) M2 segment in 100%, the M1 segment in 83%, and the internal carotid artery in 50% of thrombectomy patients. One patient demonstrated A1 segment anterior cerebral artery (ACA) enhancement, and was prospectively identified by both radiologists as having undergone ACA thrombectomy due to embolism during MCA thrombectomy. Postcontrast T1-weighted vessel wall enhancement was detected in 0% of control patients. CONCLUSION: Our findings suggest that vessel wall injuries incurred during stent-retriever thrombectomy can be detected utilizing contrast-enhanced 3 T VW-MRI. Our results further demonstrate greater endothelial injury when the thrombectomy device is oversized relative to the target vessel. Further studies are needed to evaluate the clinical significance of endothelial injury and differential effects of the device employed.